Evolving Threshold of Flood-Leading Precipitation in a User-Oriented Forecast System Based on the TIGGE Dataset - Zheng, Ziyan; Yan, Zhongwei; Chen, Jing; Han, Jiarui; Xia, Jiangjiang; Zhang, Xiaohong; Cai, Siyu; Liu, Xiaolin (Frontiers in Earth Science, 2021)
Specific users play a key role in interactive forecast systems through user-oriented information (UOI). For hydrological users, a key component of the user-oriented forecast system (UOFS) is to determine the threshold of the precipitation as a target of the forecast by considering the decision-making information at the user end. This study demonstrates a novel way of simulating the threshold of flood-leading precipitation (TFLP) via the inverse simulation of a hydrological model, combined with the flood hazard assessment in the upper reaches of the Huai River Basin, which is controlled by the Wang Jiaba (WJB) hydrological station. The flood hazard, defined as the probability of precipitation beyond the daily evolving TFLP for the next day, was evaluated based on the THORPEX Interactive Global Grand Ensemble (TIGGE) datasets, including 162 members retrieved from 5 TIGGE archive centers. After the real-time monitored water level was chosen as the UOI and integrated with the UOFS, we applied it to the flood season of 2008 as a case study to comprehensively evaluate the flood hazard generated by the UOFS and dynamically interactive UOI in the WJB sub-basin. The simulated TFLP corresponded well with the water level gap between monitored and warning values. The preliminary results of flood hazard probability showed well agreement with the first two flood peaks at 100% accuracy, while also exceeding 60% accuracy for the third flood event. Moreover, flood hazard assessments would be more detailed in their description after integration of the forecasted extreme precipitation. Overall, this study highlights the potential prospect of the usefulness of a UOFS coupled with an interactive UOI of real time water level, and provide the dynamical TFLP for flood hazard evaluation with ensemble precipitation forecast. The applicability of early flood warning by this integrated UOFS can make great sense to the operational flood prevention and mitigation.